DINAMIKA TRANSISI KEDEWASAAN DAN QUARTER LIFE CRISIS: PENGUJIAN EFEK MEDIASI RELIGIUSITAS PADA MAHASISWA TINGKAT AKHIR - Firna Aprilliani; Shinta Pratiwi; Mulya Virgonita I. Winta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The final year of undergraduate study is often marked by feelings of anxiety, indecision, and a loss of direction as students face the demands of completing their studies while transitioning into adulthood, a condition commonly referred to as a quarter-life crisis. This study aims to examine and analyze the influence of future orientation and family support on quarter-life crisis, with religiosity as an intervening variable, among final-year students at Universitas Muhammadiyah Kotabumi, North Lampung. This study employed a quantitative approach involving 120 respondents aged 18–29 years, selected through convenience sampling. Data were collected using four Likert-type psychological scales: the quarter-life crisis scale, the religiosity scale, the future orientation scale, and the family support scale. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results show that future orientation and family support each have a positive and significant effect on quarter-life crisis and on religiosity; religiosity also has a significant effect on quarter-life crisis; and religiosity significantly mediates the indirect effect of both future orientation and family support on quarter-life crisis. The research model explains 59.0% of the variance in quarter-life crisis and 65.3% of the variance in religiosity. These findings underline the importance of strengthening spiritual values as a coping mechanism for final-year students facing the transition into adulthood.